Management of abnormal uterine bleeding in perimenarche: diagnostic challenges - Muhammad Fidel Ganis Siregar (Universiti Kebangsaan Malaysia, 2016)
An 18-year-old girl—virgin, Indonesian, Bataknese, Moslem, student—was admitted to the Emergency Department of Haji Adam Malik Hospital, Medan, and presented with prolonged menstruation for the past 3 years, volume 5–6 pads/day, lasting for ±3 weeks, dark red, clotting (+), regular menstrual cycles. Vital signs were within normal limits. Physical examination revealed pale inferior conjunctiva palpebral and soft abdomen, with no palpable mass. As the patient was unmarried, speculum and vaginal examinations were not performed. This is apparently a sensitive issue as most eastern countries (including Indonesia), especially Muslim countries, highly value virginity. As the patient refused, a rectal toucher was also not used. Sonographic imaging revealed an anteflexed uterus measuring 7.1× 4.52 × 3.1 cm and endometrial thickness measuring 1.54 cm, suggestive of thickening endometrial wall. Both ovaries were normal sized. Based on these findings the patient was diagnosed with abnormal uterine bleeding and was subsequently administered with oral progesteron based on the recommended dose and duration of administration for three cycles.